A Novel PCR-Based Tool to Trace Oenological Saccharomyces cerevisiae Yeast by Monitoring Strain-Specific Nucleotide Polymorphisms - Anna Baldisseri; Davide Santinello; Sara Granuzzo; Martina Frizzarin; Fabio De Pascale; Geppo Sartori; Paolo Antoniali; Stefano Campanaro; Raffaele Lopreiato (Foods)
Saccharomyces cerevisiae plays a fundamental role in winemaking, not only driving alcoholic fermentation but also producing secondary metabolites that contribute to the organoleptic properties of wine. To ensure consistent quality and process efficiency, wineries commonly employ selected starter strains. Accordingly, the ability to control strain purity and traceability is of critical importance. Currently, the inter-delta PCR method is widely used for the strain-specific genotyping of S. cerevisiae. However, its resolution diminishes when analyzing genetically similar strains, such as those isolated from related grape types or during genotyping of large yeast collections. To address this limitation, we developed a novel strategy that integrates computational and experimental approaches to identify highly specific allelic variants (single nucleotide polymorphisms, SNPs) within the S. cerevisiae genome. Comparative genomic analysis of twenty-eight different strains led to the identification of multiple strain-specific SNPs. From these, nine SNPs spanning five strains were selected and validated through targeted PCR assays. These assays confirmed the feasibility of using SNPs as reliable genetic markers for strain discrimination and traceability. Overall, our findings demonstrate that this SNP-based approach, implemented via multiplex allele-specific (AS) PCR assays, offers a rapid, cost-effective, and highly discriminatory alternative to current genotyping methods, particularly for differentiating closely related strains.